Regional integration and industrial growth among developing countries : the case of three ASEAN members - Madani, Dorsati (Policy research working paper, 2001)
Has the revival of the Association of Southeast Asian Nations (ASEAN) in the early 1990s affected the industrial growth in Indonesia, Malaysia, and the Philippines? Perhaps not in the early years of the revival, primarily because of the countries' long history of intra-regional trade